The myth of Chinese capitalism the worker, the factory, and the future of the world - Roberts, Dexter (New York St. Martin's Press, 2020)
Dexter Roberts lived in Beijing for two decades working as a reporter on economics, business and politics for Bloomberg Businessweek. In The Myth of Chinese Capitalism, Roberts explores the reality behind today's financially-ascendant China and pulls the curtain back on how the Chinese manufacturing machine is actually powered.
Includes bibliographical references (pages 225-243) and index.
Keywords: Capitalism--China.